Community Pharmacy Minor Ailment Service (PMAS): An Untapped Resource for Children and Their Carers - Tami Benzaken; Godwin Oligbu; Michael Levitan; Subrina Ramdarshan; Mitch Blair (MDPI AG, 2021)
Background: The Pharmacy Minor Ailment Service (PMAS) was introduced in the UK over 15 years ago for use in treating minor ailments and has been shown to be effective and acceptable by the public in reducing the burden on high-cost healthcare settings (such as general practice and emergency departments). This paper aims to review the use of a PMAS in the paediatric population. Methods: PMAS was established in a London Borough in 2013. Data were collected from 33 pharmacists and 38 GPs on demographics, service utilization and costs. Results: In total, 6974 face-to-face consultations by 4174 patients were provided by pharmacies as part of the PMAS over a 12-month period. Moreover, 57% of patients were children with fever, hay fever and sore throat, accounting for 58% of consultations. Only 2% were signposted to other services. Sixty-nine percent of patients reported being seen within 5 min and 96% of patients were seen within 10 min with high levels of satisfaction. Cost savings of over GBP 192,000 were made during the scheme. Conclusions: PMAS is a highly cost effective, accessible and acceptable service for children with minor illnesses.